KONTRIBUSI TRI SENTRA PENDIDIKAN DALAM PENGUATAN NILAI-NILAI ISLAM MODERAT DI DESA LABAN MENGANTI GRESIK - Khoirul Bariyah, Lailatul; Makinuddin, Mohammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the contribution of the three pillars of education family, school, and community in reinforcing moderate Islamic values in the village Laban Menganti, Gresik. This study employs a qualitative approach using a case study design. The results indicate that families contribute to establishing the foundation of religious values through the practice of worship, setting a good example, and fostering an attitude of tolerance in daily life. Schools contribute to reinforcing moderate Islamic values through integration into the curriculum, religious activities, and fostering attitudes of mutual respect, tolerance, and non-violence within the school environment. Meanwhile, the community contributes to creating a conducive social environment through the practice of interfaith tolerance, support for educational activities, and participation in religious social activities. The findings of this study indicate that the contributions of these three educational centers complement one another in reinforcing moderate Islamic values, as evidenced by the development of tolerant attitudes, a reduction in negative behavior, and the establishment of harmonious social relationships within the community. Nevertheless, there remain limitations regarding coordination and collaboration among these educational centers. Therefore, a more structured synergy between families, schools, and the community is needed to optimize the sustainable internalization of moderate Islamic values.